Turkish validity and reliability of Burnout Syndrome Assessment Scale for nurses working in intensive care units - Yağmur Dağ; Gülsün Özdemir Aydın; Nuray Turan (BMC Nursing)
Abstract Aims This study aimed to translate the Burnout Syndrome Assessment Scale (BOSAS) for Nurses Working in Intensive Care Units into Turkish validity and reliability. Methods The questionnaire was planned to be of a methodological type and translation-back translation methods were used to translate it into Turkish. The content validity was established by submitting it to a panel of 12 faculty members with expertise in nursing. The Burnout Syndrome Assessment Scale (BOSAS) for Nurses Working in Intensive Care Units, the Maslach Burnout Inventory (MBI), and the Nurse Information Form were applied to 200 nurses. Internal consistency analyses were conducted using Cronbach’s alpha coefficients and item analysis. Confirmatory factor analysis was employed to evaluate the construct validity. To ascertain the scale’s stability over time, a test-retest method was implemented, involving the administration of a questionnaire to 150 intensive care nurses at two-week intervals. The MBI facilitated the assessment of the level of agreement between parallel forms, and intraclass correlations were computed. Results Following confirming language equivalence for the scale, the content validity index was subsequently computed. The items’ content validity indices (CVIs) ranged between 0.833 and 1.000 and were higher than the generally accepted standard level. Nevertheless, since most of the items related to the scale were explained over a single dimension, the factor analysis application was carried out over a single dimension. The MBI was used to assess the interreliability of the Burnout Syndrome Assessment (BOSAS) Scale for Nurses Working in Intensive Care Units in parallel forms. The scale’s internal consistency coefficient demonstrated a high-reliability level, achieving a value of 0.95. The intraclass correlation coefficients (ICCs) obtained for each subdimension and overall questionnaire were high. Conclusion The Turkish adaptation of this scale is a valid and reliable tool for evaluating and identifying burnout among nurses in intensive care settings.